KELAS KATA ANTONIM DALAM BAHASA BANJAR - Risarri Yayuk (TELAGA BAHASA, 2017)
Antonym study is an important part of semantic. This research problemincludes how the form of antonym in Banjarnese language based on word classes and how to prove that level of antonym based on the characteristic of the word classes. The aims of this research are to describe the form of antonym based on the word classes and to prove that level of antonym based on the characteristic of the word classes. The methodology used for data collection refers to observation method with recording and writing techniques. The data source comes from the public speech of Banjar people in Loktabat Village, Banjarbaru, South Kalimantan Province. The data were taken from January to June 2016. At the phase of analysis, the data were analyzed using the expansion technique. The results of data analysis were presented in narrative descriptive with informal and formal method. The result of this research had shown adjective class, verb, and noun. The proof of the pairs obtained is the antonym word pairs in their respective classes; it corresponds to the characteristics in each class.